(untitled) (Gestión y Gerencia, 2023)
In this work, the validity of Hubbert’s Peak is discussed, a point in time at which half of the world’s oil would have been consumed, in the context of the so-called energy transition. This quantitative and descriptive research shows that the observed trends contradict Hubbert’s basic postulates, scarcity and continuously rising prices, forcing their rethinking. Price predictions based on production and reserve estimates (supply approach) give way to a new paradigm focused on demand. From concern about exhaustion, we have moved on to the need to assign maximum importance to the negative externalities implicit in the consumption of fossil fuels, since it is imperative to stop greenhouse gas emissions. In the energy transition, the peak of demand will be crossed and the decline in the use of oil will begin with the predominance of green, abundant and cheap energies. The event should occur – if the hypotheses presented are correct – before the end of the third decade of the 21st century, although it could be delayed or anticipated. This article also comments on the Venezuelan scenario in the face of the situation, concluding that its position is relatively unfavorable.